Mortality from treatable illnesses in marginally housed adults: a prospective cohort study. Issue 8 (21st August 2015) - Jones, Andrea A; Vila-Rodriguez, Fidel; Leonova, Olga; Langheimer, Verena; Lang, Donna J; Barr, Alasdair M; Procyshyn, Ric M; Smith, Geoffrey N; Schultz, Krista; Buchanan, Tari; Krausz, Michael; Montaner, Julio S; et al.
Abstract : Objectives: Socially disadvantaged people experience greater risk for illnesses that may contribute to premature death. This study aimed to evaluate the impact of treatable illnesses on mortality among adults living in precarious housing. Design: A prospective cohort based in a community sample. Setting: A socially disadvantaged neighbourhood in Vancouver, Canada. Participants: Adults (N=371) living in single room occupancy hotels or recruited from the Downtown Community Court and followed for median 3.8 years. Main outcome measures: Participants were assessed for physical and mental illnesses for which treatment is currently available. We compared cohort mortality rates with 2009 Canadian rates. Left-truncated Cox proportional hazards modelling with age as the time scale was used to assess risk factors for earlier mortality. Results: During 1269 person-years of observation, 31/371 (8%) of participants died. Compared with age-matched and sex-matched Canadians, the standardised mortality ratio was 8.29 (95% CI 5.83 to 11.79). Compared with those that had cleared the virus, active hepatitis C infection was a significant predictor for hepatic fibrosis adjusting for alcohol dependence and age (OR=2.96, CI 1.37 to 7.08). Among participants <55 years of age, psychosis (HR=8.12, CI 1.55 to 42.47) and hepatic fibrosis (HR=13.01, CI 3.56 to 47.57) were associated with earlier mortality. Treatment rates for these illnesses were low (psychosis: 32%, hepatitis C virus: 0%) compared with other common disorders (HIV: 57%, opioid dependence: 61%) in this population. Conclusions: Hepatic fibrosis and psychosis are associated with increased mortality in people living in marginal conditions. Timely diagnosis and intervention could reduce the high mortality in marginalised inner city populations.